Control of electron acceleration process during merging start-up of spherical tokamak. (14th October 2021) - Inomoto, M.; Mihara, T.; Kondo, K.; Kaneko, H.; Kusano, K.; Kaneko, K.; Maeda, Y.; Shinohara, A.; Jin, H.; Suzuki, T.; Tanabe, H.; Ono, Y.; et al.
Abstract: The axial plasma merging method is one of the start-up schemes to form spherical tokamak (ST) plasma without use of a center-solenoid coil. It involves a magnetic reconnection process in the presence of high toroidal magnetic field parallel to the reconnection electric field and has the potential to accelerate electrons directly along the magnetic field lines. In the paper, the role of boundary conditions of the reconnection downstream region was investigated in the UTST experiment. Self-generated axial electric field in the reconnection downstream region was observed to grow up to 20–30 times as large as the toroidal electric field where the MHD condition holds, but was largely suppressed inside the area where the magnetic field lines are contacted to the inboard limiter conductors equipped on the center stack. This suppression effect was attributed to the short circuit connection of the magnetic field lines to hinder the axial charge separation and then a significant part of the parallel electric field remained. These experimental results suggest that the merging start-up method has the capability to enhance electron acceleration efficiency by magnetic reconnection and may have the potential to produce high electron temperature ST plasma applicable for additional heating and current drive techniques.